Decision Making in Choosing Independent Auditors for Conducting Initial Audit Using Analysis Hierarchy Process for one of the Exporter Company in Australia - Rahman, Muhammad Ali; Siallagan, Manahan (International Journal of Social Service and Research, 2025)
The Australian live cattle export industry to Indonesia operates under a stringent regulatory framework, the Exporter Supply Chain Assurance System (ESCAS), which mandates Independent Initial Audit Reports (IIAR) for new facilities. A critical challenge for exporters is the selection of a competent independent auditor, a decision often made informally, leading to risks of audit failure, cost overruns, and shipment delays. This study addresses this gap by applying the Analytical Hierarchy Process (AHP) to develop a structured, multi-criteria decision-making model for auditor selection.The research identified four key selection criteria through expert interviews: Flexibility in Time, Credibility, Cost per Facility, and Experience in the Field. Pairwise comparisons by industry experts determined the priority weights, revealing Flexibility in Time as the most critical factor (55.8%), followed by Credibility (26.3%). Three auditor firms were evaluated against these criteria. The AHP analysis calculated global priority scores, ranking Auditor A first (38.4%) due to its exceptional flexibility, which is paramount for mitigating supply chain disruption risks. Auditor B ranked second (35.9%), valued for its strong credibility, while Auditor C (25.7%) was deemed unsuitable despite its low cost due to inflexibility.The study concludes that a structured AHP model effectively transforms a subjective decision into a transparent, defensible process. The findings recommend selecting Auditor A, prioritizing operational resilience and regulatory security over short-term cost savings. This approach provides exporters with a robust framework to ensure compliance, protect market access, and enhance strategic decision-making in a high-stakes industry.